Examining the association of clinician characteristics with perceived changes in cervical cancer screening and colposcopy practice during the COVID-19 pandemic: a mixed methods assessment - Lindsay Fuzzell; Naomi C Brownstein; Holly B Fontenot; Paige W Lake; Alexandra Michel; Ashley Whitmer; Sarah L Rossi; McKenzie McIntyre; Susan T Vadaparampil; Rebecca B Perkins (eLife, 2023)
Background: The COVID-19 pandemic led to reductions in cervical cancer screening and colposcopy. Therefore, in this mixed method study we explored perceived pandemic-related practice changes to cervical cancer screenings and colposcopies. Methods: In 2021, a national sample of 1251 clinicians completed surveys, including 675 clinicians who performed colposcopy; a subset (n=55) of clinicians completed qualitative interviews. Results: Nearly half of all clinicians reported they were currently performing fewer cervical cancer screenings (47%) and colposcopies (44% of those who perform the procedure) than before the pandemic. About one-fifth (18.6%) of colposcopists reported performing fewer LEEPs than prior to the pandemic. Binomial regression analyses indicated that older, as well as internal medicine and family medicine clinicians (compared to OB-GYNs), and those practicing in community health centers (compared to private practice) had higher odds of reporting reduced screening. Among colposcopists, internal medicine physicians and those practicing in community health centers had higher odds of reporting reduced colposcopies. Qualitative interviews highlighted pandemic-related care disruptions and lack of tracking systems to identify overdue screenings. Conclusions: Reductions in cervical cancer screening and colposcopy among nearly half of clinicians more than 1 year into the pandemic raise concerns that inadequate screening and follow-up will lead to future increases in preventable cancers. Funding: This study was funded by the American Cancer Society, who had no role in the study’s design, conduct, or reporting.